Tuberkulosis Kutis Verukosa pada Pasien Tuberkulosis Paru - Mimi Maulida; Nanda Earlia; Vella Vella; Karamina Maghfirah (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2023)
Cutaneous tuberculosis is a skin disorder caused by Mycobacterium tuberculosis, commonly classified according to its spreading route into endogenous, exogenous, and hematogenous, with distinct skin morphology and histopathological findings. Tuberculosis verrucosa cutis is a classification form of cutaneous tuberculosis, a paucibacillary disease caused by exogenous reinfection (inoculation) after sensitization on an immunocompromised individual. Management of cutaneous TB is generally similar to the management of pulmonary TB. In this paper, we presented a case of 62 years old male with a purplish rough patch on the right dorsum of the foot that began 1,5 years. There is a history of trauma and pulmonary TB. On the right dorsum of the foot, we identified a verrucous lesion with a livid base, irregular with the size of 6x3 cm. The diagnosis is established based on clinical features and histopathology evaluation. The patient received treatment with antituberculosis medication, topical mupirocin ointment 2%, and vaseline petroleum jelly. Improvement of the lesions was observed after the patient completed the intensive phase in two months of treatment with antituberculosis drugs.